2021
DOI: 10.1111/jocs.15298
|View full text |Cite
|
Sign up to set email alerts
|

Does the clinical effectiveness of Mitraclip compare with surgical repair for mitral regurgitation?

Abstract: Background Surgical repair of the mitral valve has long been the established therapy for degenerative mitral regurgitation (MR). Newer transcatheter methods over the last decade, such as the MitraClip, serve to restore mitral function with reduced procedural burden and enhanced recovery. This study aims to compare the shortterm and midterm outcomes of MitraClip insertion with surgical repair for MR. Methods A systematic review of the literature was conducted for studies comparing outcomes between surgical repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 38 publications
(67 reference statements)
0
35
0
Order By: Relevance
“…Although most of articles record the left ventricular ejection fraction (LVEF) values before, due to the large clinical heterogeneity between the studies, the postoperative EF value was not included in the outcome indicators for comparison. A Meta study in China [35] once reported that the Percutaneous Mitral Valve Clipping (Mitra-Clip treatment) can improve the cardiac function of patients with mitral regurgitation and heart failure to a certain extent, but further studies are still needed to prove its conclusions; recent studies by Khader [36] and others in the UK have also repeatedly emphasized the mid-term durability of MR valve surgical repair is better than Mitra-Clip.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of articles record the left ventricular ejection fraction (LVEF) values before, due to the large clinical heterogeneity between the studies, the postoperative EF value was not included in the outcome indicators for comparison. A Meta study in China [35] once reported that the Percutaneous Mitral Valve Clipping (Mitra-Clip treatment) can improve the cardiac function of patients with mitral regurgitation and heart failure to a certain extent, but further studies are still needed to prove its conclusions; recent studies by Khader [36] and others in the UK have also repeatedly emphasized the mid-term durability of MR valve surgical repair is better than Mitra-Clip.…”
Section: Discussionmentioning
confidence: 99%
“…1 The disease is categorized into primary (also called degenerative) or secondary (also called functional), where primary MR is caused by an abnormality of 1 or more components of the valve apparatus (e.g., leaflets, papillary muscles, annulus); whereas, secondary MR is due to another heart disease such as coronary heart disease, cardiac ischemia, and heart failure. 2,3 MR is a progressive disease and considered the second most frequent valve disease. 1,4 The incidence of MR increases with age, with a prevalence of over 9% in patients ≥ 75 years of age.…”
Section: Context and Policy Issuesmentioning
confidence: 99%
“…Three of the included SRs were published in 2021 3,4,8 while 1 was published in 2020. 13 Each SR was based on relevant literature retrieved by systematic searches conducted in multiple databases (i.e., 2 or more) between December 2018 and June 2020.…”
Section: Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations